Design Principles of Clinical Dashboards Incorporating PROMs: Crafting and Elaborating the Potential of Clinical Dashboards Incorporating PROMs - Anja Bischof; Irene Salvi; David Kuklinski; Justus Vogel; Alexander Geissler (Universität St.Gallen, School of Medicine, Lehrstuhl für Management im Gesundheitswesen, 2023)
Objectives: A clinical dashboard is a data-driven clinical decision support tool visualizing mul-tiple key performance indicators in a single report while minimizing time and effort for data gat-hering. Evidence showed that including patient-reported outcome measures (PROMs) in clinical dashboards supports the clinician's understanding of how treatments impact patients' health sta-tus and helps identifying health-related quality of life changes at an early stage. While existing literature mainly focused on the benefits of using disease-specific PROMs in clinical dashboards, the EQ-5D has rarely been investigated despite its potential to assess the patient's overall health status and mental well-being. To address this gap, we aimed to determine design principles for clinical dashboards incorporating generic - i.e., the EQ-5D - and disease-specific PROMs. Methods: We used a three-step approach. First, a scoping literature review summarized the evi-dence of relevant design principles for clinical dashboards in general. Second, insights from inter-views with both software producers and users of clinical dashboards validated and enhanced the results of the literature review. Third, we built dashboard prototype using the knowledge ga-thered in the first two steps, which was finally evaluated by a focus group discussion. Results: We found that the design principles for clinical dashboards do not have to change between different episodes of care. The scoping literature review highlighted to incorporate vari-ous relevant design principles into clinical dashboards, such as patient data, clinical metrics, past PRO assessment scores, or peer-group comparison. Interviews showed that both software pro-ducers and users had similar views on clinical dashboard use, primarily for patient monitoring and interpretation support of PRO data. However, their opinions diverged on the key users, while users favored specialists, dashboard producer expressed their favor for a broader user base. During the focus group discussion, participants found clinical dashboards incorporating PROMs valuable, highlighting the importance getting the possibility of finally considering patients' self-reported health status during consultations. Design principles derived from literature and inter-views aligned with the views expressed during focus group discussions, emphasizing the use of both generic and disease-specific PROMs. Conclusion: The chosen three-step approach permitted cross-checking the state-of-the-art in lite-rature and detecting white spots where users and software producers showed diverging tenden-cies for certain design principles. Our research confirmed that the design principles for different disease areas do not differ. The past score PROM assessment and peer-group comparison were rated, by both the software producers and the users, as the most valuable design principles. Ulti-mately, this research aims to inform the development of clinical dashboards incorporating PROMs.
Keywords: I10; I19; 330; Clinical dashboards; Patient-reported outcome measures; PROMs